A novel Wnt5a‐Frizzled4 signaling pathway mediates activity‐independent dendrite morphogenesis via the distal PDZ motif of Frizzled 4. Issue 8 (1st December 2014) - Bian, Wen‐Jie; Miao, Wan‐Ying; He, Shun‐Ji; Wan, Zong‐Fang; Luo, Zhen‐Ge; Yu, Xiang
ABSTRACT The morphology of the dendritic tree is critical to neuronal function and neural circuit wiring. Several Wnt family members have been demonstrated to play important roles in dendrite development. However, the Wnt receptors responsible for mediating this process remain largely elusive. Using primary hippocampal neuronal cultures as a model system, we report that Frizzled4 (Fzd4), a member of the Fzd family of Wnt receptors, specifically signals downstream of Wnt5a to promote dendrite branching and growth. Interestingly, the less conserved distal PDZ binding motif of Fzd4, and not its conserved proximal Dvl‐interacting PDZ motif, is required for mediating this effect. We further showed that Dvl signaled parallel to and independent of Fzd4 in promoting dendrite growth. Unlike most previously described pathways, Wnt5a/Fzd4 signaling promoted dendrite development in an activity‐independent and autocrine fashion. Together, these results provide the first identification of a Wnt receptor for regulating dendrite development in the mammalian system, and demonstrate a novel function of the distal PDZ motif of Fzd4 in dendrite morphogenesis, thereby expanding our knowledge of the complex roles of Wnt signaling in neural development. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 805℃822, 2015